Globular adiponectin acts as a melanogenic signal in human epidermal melanocytes. (4th July 2018) - Kim, Y.; Cho, J.Y.; Oh, S.W.; Kang, M.; Lee, S.E.; Jung, E.; Park, Y.S.; Lee, J.
Summary: Background: Adiponectin is an adipocyte‐derived cytokine that circulates as a full‐length protein and a fragment containing the globular domain of adiponectin (gAd). A recent study has reported the antimelanogenic effects of full‐length adiponectin. Objectives: To examine the involvement of gAd in melanogenesis and its mechanisms of action. Methods: The effects of gAd on melanogenesis and its mechanisms of action were investigated in human epidermal melanocytes and reconstructed epidermis, including melanin content, cellular tyrosinase activity, cyclic adenosine monophosphate (cAMP) production and protein kinase A (PKA) activity, expression and phosphorylation of signalling molecules. Results: Exogenous gAd increased melanin content, and the mRNA levels of microphthalmia‐associated transcription factor (MITF) and its downstream genes TRP1, but not TRP2, were increased by gAd. However, cAMP production and PKA activity were not affected by gAd. Moreover, attempts to elucidate the underlying mechanism behind the gAd‐mediated effect revealed that gAd could regulate melanogenesis by upregulating MITF through phosphorylation of the cAMP response element‐binding protein (CREB). In addition, upregulation of MITF was mediated by activation of adenosine monophosphate‐activated protein kinase (AMPK)–p38 mitogen‐activated protein kinase (MAPK) signalling. Taken together, these findings indicate that promotion of melanogenesis by gAd occurs through increased expression of MITF, which is mediated by activation of the AMPK–p38 MAPK–CREB pathway. Conclusions: These findings suggest that gAd contributes to epidermal homeostasis via its effect on melanocyte biology, and products of adipose tissue could affect epidermal biology. Abstract : What's already known about this topic? Adiponectin exists both as a full‐length 30‐kDa protein and a fragment containing the globular domain of adiponectin (gAd). gAd and full‐length adiponectin have been reported to mediate the tissue‐specific effects and to regulate distinct signalling pathways and end‐point responses in the same tissue. A previous study reported that full‐length adiponectin inhibits melanogenesis. However, the effects of gAd on melanogenesis have not been investigated. What does this study add? This study demonstrated that, unlike full‐length adiponectin, gAd promotes melanogenesis, and this occurs through increased expression of MITF, which is mediated by activation of the adenosine monophosphate‐activated protein kinase–p38 mitogen‐activated protein kinase–cyclic adenosine monophosphate response element‐binding protein pathway. What is the translational message? This study demonstrated that gAd contributed to the normalization of abnormal melanogenesis by promoting melanogenic events. If these findings are confirmed by clinical studies, gAd may be useful for the control of hypopigmented skin diseases that occur as a result of reduced melanin synthesis. Linked Comment:  Tobin. Br J Dermatol 2018;179 :561–562 . Respond to this article